Torsional travelling wave reflection in the bar with an artificial defect - Khakimov, Akim Gayfullinovich (Computational Continuum Mechanics, 2012)
Reflection and propagation of a torsional wave in an infinite bar with an artificial transverse defect are investigated. Dependence of the reflected wave on the damage parameters is obtained. The solution of the inverse problem allows us to determine the damaged region coordinate and the parameter, including damage depth and length, based on the characteristics of falling and reflected waves at the sighting point.
Keywords: rod; torsional wave; direct and inverse problems